How to make “Value Flow” for a Start-up Enterprise - Beelaerts van Blokland, W. A.; Dumitrescu, B.; Curran, R. (Cranfield University Press, 2009)
This paper is about research towards the design of a start-up organization “OpDieFiets.nl”. The start up focuses on market demand for quality bicycles at the lowest price possible for the Dutch market. Theories around innovation and value systems form the background of designing the organization. The 3C value flow model currently in development defines the core value drivers for enterprises and is used to pre-design the value system for OpDieFiets.nl. Four other start-up companies were investigated with help of the 3C value flow model to define the value system for OpDieFiets.nl.
Organised by: Cranfield University
Keywords: 3C value flow model; Low-cost; Value networks; Lean manufacturing; Start-ups; Bicycle